Elemental profiling of surface water around Dhaka city by laser induced breakdown spectroscopy - Ahmed, MF; Abedin, KM; Sadat, ME; Talukder, AI; Wahadoszamen, M; Haider, A F M Yusuf (© 2009 Journal of Bangladesh Academy of Sciences, 2017)
This article was published in the Journal of Bangladesh Academy of Sciences [© 2009 Journal of Bangladesh Academy of Sciences] and the definite version is available at: http://dx.doi.org/10.3329/jbas.v33i2.4104